The Mediating Role of Change Management Between Technology Readiness and Job Performance - Samer Hamad (European Scientific Journal, ESJ, 2025)
This research investigates the interaction between technology readiness, change management, and job performance. The research explored the effects of technology readiness on change management and job performance, as well as the mediating role of change management in this relationship. A self-report questionnaire was distributed to obtain a representative sample, yielding 409 complete responses. All questions were mandatory to prevent missing data. The survey began with demographic items (age, gender, education, years spent in the organization tenure, and work experience) followed by validated scales: Technology readiness (optimism and innovativeness), Change management (leadership support and participation/communication), Job performance (perceived organizational support and work-life conflict).A Structural Equation Modeling (SEM) approach was selected for its unique advantages in testing complex theoretical relationships. The results indicated that technology readiness had no significant direct effect on change management or job performance and change management did not significantly mediate job performance. These results revealed that the widely accepted link between technology readiness and change management may be more context-dependent than previously assumed. The findings suggest that in organizational settings where change is mandated rather than voluntary, individual readiness may become less influential. These insights suggest organizations should focus on structural implementation factors over individual preparation when managing technological changes, offering a new perspective for both research and practice in organizational change management.